2021
DOI: 10.1109/access.2021.3069712
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Electromagnetic Head Imaging System Using Metamaterial Loaded Compact Directional 3D Antenna

Abstract: A non-invasive, low-powered, and portable electromagnetic (EM) head imaging system is presented using metamaterial (MTM) loaded compact directional 3D antenna. The antenna consists of two slotted dipole elements with 2×3 and 3×3 finite MTM array elements in top and ground, respectively, and folded parasitic elements that operate within the frequency range of 1.12 GHz to 2.5 GHz. The MTM array elements are optimized to enhance the overall performance regarding antenna bandwidth, realized gain, efficiency, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Currently used imaging systems widely used in medical healthcare such as CT scans, MRI, ultrasound, and X-rays are very bulky, costly, and not accessible in rural areas. These bulky systems are not movable to specific locations for diagnosis purposes [ 45 ]. Portable and wearable health-monitoring devices are the only solution to minimize the distance between the patient and the physician.…”
Section: Flexible Electronics and Portable Systemsmentioning
confidence: 99%
“…Currently used imaging systems widely used in medical healthcare such as CT scans, MRI, ultrasound, and X-rays are very bulky, costly, and not accessible in rural areas. These bulky systems are not movable to specific locations for diagnosis purposes [ 45 ]. Portable and wearable health-monitoring devices are the only solution to minimize the distance between the patient and the physician.…”
Section: Flexible Electronics and Portable Systemsmentioning
confidence: 99%
“…In this research, an experimental sensor-based microwave brain imaging (SMBI) system has been developed to generate microwave brain images and analyze the system’s performance. The SMBI system framework has been implemented by our research group, as reported in [ 23 , 46 ]. It is worth mentioning here that a wideband antenna sensor with a high gain and unidirectional characteristics is required with a frequency band of 1 to 4 GHz for the SMBI system [ 11 , 12 , 15 , 24 , 25 ].…”
Section: Experimental Setup Of a Sensor-based Microwave Brain Imaging...mentioning
confidence: 99%
“…The collected signals from the PNA were preprocessed by the MATLAB programming language. Thereafter, an image reconstruction algorithm, M-DMAS (modified delay-multiply-and-sum) [ 23 ] was utilized to produce the desired RMW brain images of the head regions. The frequency range of 1.43 GHz to 3.71 was considered for image reconstruction.…”
Section: Experimental Setup Of a Sensor-based Microwave Brain Imaging...mentioning
confidence: 99%
See 1 more Smart Citation
“…The brain stroke, which occurs due to the presence of blood clots in the head, blocks the transportation of oxygen, thus interrupting the biological activity of the human body and possibly inducing paralysis. Hence, a fast diagnosis is required for this circumstance because it may endanger the life of a patient [1], [2]. Therefore, head imaging is crucial due to its role in performing early diagnosis and detection.…”
Section: Introductionmentioning
confidence: 99%